Application of Accelerometers in Sports Training - Lin, A.; Mullins, R.; Pung, M.; Theofilactidis, L.
The work this term enabled the analysis of accelerometer performance to see if Analog Devices' accelerometers could be applicable to sports training. The deliverables were achieved: 1) The project developed a characteristic signal from the data collected, and 2) The project showed a direct relationship between a specific physical movement and outputted data, that can identify good and bad technique. With further work, the use of accelerometers in sports training is promising, and therefore, it is recommended that continuing study be performed in the use of accelerometers in sports training products.